Structural modification and ultra-high coercivity of nanostructural anisotropic MnBi/Bi films. (15th April 2017) - Zhang, Yinfeng; Han, Jingzhi; Liu, Shunquan; Tian, Haidong; Zhao, Hui; Du, Honglin; Yang, Yingchang; Fang, Yikun; Li, Wei; Yang, Jinbo
Abstract: Nanostructural anisotropic MnBi films with strong out-of-plane orientation were prepared by pulsed laser deposition and subsequent heat treatment. The orientation and particle size of MnBi films can be controlled by altering those of the Bi template-layers. Under the optimal treatment, a room temperature coercivity as high as 27.4 kOe was obtained in the nanostructural MnBi films. This high coercivity stems from the complete isolation in Bi matrix of refined MnBi clusters, within which MnBi nanoparticles are magnetically coupled. As the size of MnBi clusters decreases, the magnetization process of the nanostructural MnBi films changes from non-uniform rotation to uniform rotation of magnetic moments. Graphical abstract: Image